Sistem Pendukung Keputusan Penyaluran Bantuan Balita Stunting Menggunakan Metode SAW (Simple Additive Weighting) Studi Kasus Posyandu Mawar - Herlina Vika Safriyani; Khalimaturrofi’ah; Purwanto (Journal Of Informatics And Busisnes, 2025)
Stunting in toddlers is a chronic malnutrition that impacts child growth and development. This study aims to develop a Decision Support System for Distribution of Stunting Toddler Assistance Using the SAW (Simple Additive Weighting) Method at the Mawar Dukuh Tambakan Integrated Health Post (Posyandu). This system was developed to assist Posyandu cadres in determining toddler assistance recipients more objectively and efficiently. The selection process that has been carried out manually is at risk of errors in recording, inaccurate data and errors in determining assistance for stunted toddlers. Therefore, a system is needed that is able to assess based on various criteria in a structured manner. This system was designed using the waterfall development method with stages of needs analysis, system design, implementation, and testing. The research method used is a qualitative method, namely using observation, documentation, and interviews. At the design stage, namely star UML for system modeling, figma for interface design. Frontend uses HTML, CSS, Javascript. Backend uses PHP, Database uses MYSQL, XAMPP as a local web server and Visual Studio Code as the main editor. Testing uses blackbox and a Likert scale questionnaire. The results of the study show that the system can help the selection process for aid recipients quickly, accurately and objectively. Based on the questionnaire evaluation with a Likert scale, the system received a user satisfaction percentage of 86.4%.